Effect of certain extenders on semen quality of boars during preservation at 17°C - KUMAR, S; SINGH, A K; DHINDSA, S S; SINGH, P (The Indian Journal of Animal Sciences, 2023)
The present study was designed to determine the effect of three selected extenders on liquid preservation of boar semen at 17°C. Ejaculates (30) were collected from three boars (one ejaculate/boar/week) housed at University pig farm, Ludhiana using dummy sow. Only ejaculates having >70% initial progressive motility were extended in Beltsville Thawing Solution (BTS), Safe Cell (SFC) and Tris-Egg Yolk (TEY) extenders in the ratio 1:4 and preserved in a BOD incubator at 17°C for 120 h. The semen was evaluated for different sperm attributes and lipid peroxidation (MDA) at 0, 24, 48, 72, 96 and 120 h of preservation. The mean percentage of sperm motility, viability, plasma membrane integrity and acrosome integrity were significantly higher in BTS as compared to SFC and TEY at different hours of storage period. At 120 h of preservation, highest percentage of in vitro capacitation/acrosome reaction was seen in semen stored in BTS followed by SFC and lowest in TEY after 6 h of incubation. Eventually, significantly lower levels of MDA were noticed in semen extended in BTS than in their contemporary extenders (SFC and TEY) at 96 and 120 h of storage period. The mean percentage of most sperm parameters decreased gradually from day of collection (0 h) up till 120 h in all the extenders. In conclusion, Beltsville Thawing Solution was better than Safe Cell and Tris-Egg Yolk extenders in liquid preservation of boar semen at 17oC owing to improved sperm characteristics and reduced oxidative stress.